2012
DOI: 10.1155/2012/418289
|View full text |Cite
|
Sign up to set email alerts
|

Relative Preservation of Advanced Activities in Daily Living among Patients with Mild-to-Moderate Dementia in the Community and Overview of Support Provided by Family Caregivers

Abstract: Little is known about the extent to which advanced activities of daily living among patients with dementia are preserved and how family caregivers of these patients support them in the community. In this cross-sectional assessment of pairs of patients with dementia and their family caregivers, we evaluated basic, instrumental, and advanced activities of daily living by comparing past and present status observed by caregivers with subjective estimations by patients with dementia. We also asked about ways in whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 22 publications
0
29
0
5
Order By: Relevance
“…Advanced ADL were also reduced, with a medium effect size for the impact of dementia. It has been suggested that this reduction may happen early in the course of dementia, as these abilities can be impaired by subtle cognitive changes (Vriendt et al ., ), but, similar to our study, advanced ADL have been found to be less reduced than instrumental ADL in dementia (Takechi et al ., ). These results indicate that impairments in instrumental ADL are a hallmark of dementia, while loss of advanced ADL may also happen as a result of behavioural disturbance and milder causes of cognitive impairment.…”
Section: Discussionmentioning
confidence: 97%
“…Advanced ADL were also reduced, with a medium effect size for the impact of dementia. It has been suggested that this reduction may happen early in the course of dementia, as these abilities can be impaired by subtle cognitive changes (Vriendt et al ., ), but, similar to our study, advanced ADL have been found to be less reduced than instrumental ADL in dementia (Takechi et al ., ). These results indicate that impairments in instrumental ADL are a hallmark of dementia, while loss of advanced ADL may also happen as a result of behavioural disturbance and milder causes of cognitive impairment.…”
Section: Discussionmentioning
confidence: 97%
“…The causes of disruptive vocalisation in people with dementia, although largely unknown, are often linked to pain, over or under stimulation, anxiety or distress from an unfamiliar situation (Woods & Diamond, ; Attix & Welsh‐Bohmer, ). When the needs of people with dementia are unmet, behaviours such as disruptive vocalisation are expressed as the way to communicate (Algase et al ., ; Takechi et al ., ). It is often deemed that people with dementia engage in such disruptive behaviour because they express their pain, stress and anxiety needs poorly (Kitwood, ; Casey, ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, risky behaviors, known to be a source of anxiety for the caregiver, were summed with accidents in order to have a measure for the outcome variable that could be analyzed statistically. Epidemiologic studies, reported in the literature review, establish the higher rate of accidents and injuries in this population of persons with DAT or a related disorder [12–14, 18, 19]. …”
Section: Resultsmentioning
confidence: 99%
“…Even in early stages of memory loss, if a person is unaware of memory loss, they are more likely to have difficulty with everyday decisions such as medication management [18]. In addition, patients' self-evaluations of their ability to conduct instrumental activities of daily living (IADL) such as medication management and ability to use the telephone are significantly higher than caregivers' objective evaluations [19]. …”
Section: Introductionmentioning
confidence: 99%